Study of Venation of leaf using Image Processing - Borah, Agnimitra (International Journal of Computer Sciences and Engineering, 2025)
In this work, various edge detection techniques have been implemented on an image of a leaf taken under different light conditions to study the venation pattern of that leaf. The efficiency and the accuracy of these techniques in detection of the veins have been compared and analyzed. Edge detection operators such as Sobel and Canny edge detectors have also been implemented in the leaf image to identify the difference between the two. Step edges and ridge edges have been found out by taking the Gaussian and the first and second order derivative of the Gaussian of the image. The experimental result showed that canny edge detectors have been more accurate and can detect the veins more precisely with more details as compared to other techniques.